A dual continuum model of the reasons for use of complementary health approaches among overweight and obese adults: findings from the 2012 NHIS - Dawn M. Upchurch; Linghui Liang; Fuschia M. Sirois (BMC, 2018)
Abstract Background Obese and overweight individuals have greater illness and disease burden, but previous findings from the 2002 National Health Interview Survey (NHIS) suggest that they are no more likely to use complementary health approaches (CHA) than those of normal weight. The current study investigates the relationship between weight status and CHA use, and among CHA users, examines differences in reasons for use by weight status. We propose and test a Dual Continuum Model of Motivations for Use of CHA to examine differences in reasons for use by weight status. Method Participants were drawn from the 2012 NHIS, a nationally representative sample of civilian, non-institutionalized US adults (N = 34,525). Weight status was operationalized by body mass index. CHA use was measured in the past year and was categorized into alternative providers, products, and practices. Among CHA users (N = 9307) factors associated with use were categorized as health enhancing or health reactive. Results Logistic regression showed overweight and obese individuals were less likely to use alternative providers, products, and practices than normal weight. Multinomial logit regression showed some support that overweight and obese adults were less likely than normal weight persons to use CHA for health-enhancing reasons, and more likely to use for health reactive reasons. Conclusions Despite greater health burden, overweight and obese adults are underutilizing CHA, including modalities that can be helpful for health management. The Dual Continuum Model of CHA Motivations shows promise for explicating the diversity of reasons for CHA use among adults at risk for health problems.